2008
DOI: 10.1111/j.1742-4658.2008.06745.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of adenine anchoring and ion pairing at the coenzyme B12‐binding site in diol dehydratase catalysis

Abstract: Adenosylcobalamin (AdoCbl) is a cofactor for enzymatic radical reactions, including carbon skeleton rearrangements, heteroatom eliminations, and intramolecular amino group migrations [1][2][3]. These reactions involve the migration of a hydrogen atom from one carbon atom of the substrate to the adjacent carbon atom [4,5] in exchange for group X, which moves in the opposite direction [6]. The reactions are initiated by abstraction of a hydrogen atom from substrates with an adenosyl radical that is generated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Thep resent structures of DD complexed with AdoCbl indicated that Thra172 and Sera224 are key residues for stabilizing the post-homolysis state of the adenosyl group in DD.W en ext investigated the importance of the hydrogen bonds involving these two residues for catalytic properties by site-directed mutagenesis.A mong all of the present and reported mutants of the residues, [23] the Ta172A mutant displayed the lowest k cat value and k cat /k inact ratio ( Table 1). The k cat /k inact ratio indicates the average number of catalytic turnovers before inactivation.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Thep resent structures of DD complexed with AdoCbl indicated that Thra172 and Sera224 are key residues for stabilizing the post-homolysis state of the adenosyl group in DD.W en ext investigated the importance of the hydrogen bonds involving these two residues for catalytic properties by site-directed mutagenesis.A mong all of the present and reported mutants of the residues, [23] the Ta172A mutant displayed the lowest k cat value and k cat /k inact ratio ( Table 1). The k cat /k inact ratio indicates the average number of catalytic turnovers before inactivation.…”
mentioning
confidence: 50%
“…Consistently,t he lower k cat /k inact value indicates that the mutant enzyme is more prone to be inactivated than the wild type,s uggesting that the positionally-unstable adenosyl radical in the Ta172A mutant causes undesirable side reactions at greater probability than does the wild type.T he importance of the hydrogen bond for catalysis is also supported by kinetic studies using the Ta172S mutant. [23] Previous biochemical study using AdoCbl monocarboxylate isomers,i nw hich one of the propionamide side chains was hydrolyzed, indicated that coenzyme activity in DD decreases in the order d-isomer > e-isomer > b-isomer. Indeed, the k cat value of the mutant decreased but still retained 10 %that of the wild type (Table 1).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Indeed, the k cat value of the mutant decreased but still retained 10 %that of the wild type (Table 1). TheS era224 mutants,i ncluding previously reported ones, [23] showed relative k cat values ranging from 3% to 19 %a gainst the wild type enzyme.O ne explanation for the decrease of the k cat values upon mutation is due to complete or partial loss of their hydrogen bond interactions with 2'-OH of the ribose group and/or improper positioning of the adenosyl radical caused by the decrease or increase in steric hindrance by the volume change of the side chain. Another possible explanation is that the reduction of the anchoring effect on the adenine moiety is caused by the loss of the hydrogen bond interaction and destabilizes the post-homolysis state of the adenosyl group.…”
Section: Angewandte Chemiementioning
confidence: 69%
“…Indeed, the structure of the mutant DD(Ta172A)/1,2-PDO reveals that electron density corresponding to the ribose moiety of the adenosyl group is not visible (Supporting Information, Figure S2c), suggesting that the hydrogen bonds between Thra172 and the a-side chain of the corrin ring and between the a-side chain and 3'-OH of the ribose group in the post-homolysis state are crucial for holding the adenosyl [a] From ref. [23].…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation